THE INFLUENCE OF LIQUIDITY, ACTIVITY, AND SOLVENCY ON STOCK PRICES WITH PROFITABILITY AND CORPORATE SOCIAL RESPONSIBILITY DISCLOUSURE AS INTERVING VARIABLES IN THE RESTAURANT, HOTEL AND TOURISM SUB-SECTOR - Weny Astutik; Mulyanto Nugroho; Nekky Rahmiyati (International Journal Labs, 2022)
The purpose of this study was to determine the effect of liquidity, activity, and solvency on stock prices by using two intervening variables, namely profitability and CSRD. This research uses the causal explanatory method which is a type of research where the researcher explains the causal relationship between the variables through hypothesis testing, namely testing hypotheses based on the theory that has been formulated previously, and then the data that has been obtained is calculated through a quantitative approach. Liquidity has no significant effect on Profitability, Liquidity has no significant effect on CSRD, Liquidity has no significant effect on Stock Price, Activity has no significant effect on Profitability, Activity has no significant effect on CSRD, Activity has no significant effect on Stock Price, Solvency has no significant effect on Profitability, Solvency has no significant effect on CSRD, Solvency has no significant effect on stock prices, profitability has no significant effect on stock prices, CSRD has no significant effect on stock prices.